PENGARUH MODEL PEMBELAJARAN PEER INSTRUCTION FLIP DAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATERI SISTEM EKSKRESI - Rusdi Rusdi; Dian Evriyani; Dwi Khaerunnisa Praharsih (Biosfer: Jurnal Pendidikan Biologi, 2016)
Achievement of learning process can be seen from student cognitive learning outcome. Learning model plays an important role in student cognitive learning achievement. The introduction and implementation of Peer Instruction Flip model and Flipped Classroom are expected to increase the cognitive learning outcomes of students. The research was conducted in SMAN 6 Tangerang on Mei-Juni 2015. The reseach method used was a quasi experiment. The research sample used was XI MIA 1 (Peer Instruction Flip model) and XI MIA 3 (Flipped Classroom model) and XI MIA 2 (STAD model) who collected by Simple Random Sampling. Prerequisite test analysis of normality was the Kolmogorov-Smirnov and homogeneity test with the Bartlett test. Based on calculation, data obtained was normally distributes and homogeneously. The statistical hypothesis with Anava one way test result on rejected null hypothesis at Î± 0,05. It can be concluded that there was effect of Peer Instruction Flip and Flipped Classroom learning model toward student cognitive learning outcome in Excretory System material.